2008
DOI: 10.1177/039463200802100117
|View full text |Cite
|
Sign up to set email alerts
|

Role of Fosfomycin Tromethamine in Modulating Non-Specific Defence Mechanisms in Chronic Uremic Patients towards ESBL-Producing Escherichia Coli

Abstract: Antimicrobial agents and polymorphonuclear cells (PMNs) have the potential to interact in such a way that improve the therapy for infectious diseases. In immunocompromised patients highly susceptible to microbial infections with high morbidity and mortality, several metabolic and functional alterations in PMNs, mostly related to microbicidal activity, are observed. Therefore, the antibiotic of choice should have a good antimicrobial effect without impairing host defences. The aim of this study is to evaluate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 22 publications
1
34
0
Order By: Relevance
“…There is some evidence that fosfomycin might be a promising solution for the treatment of such infections (19,20,30). It is also suggested that the antimicrobial activity of fosfomycin against ESBL-producing E. coli may be accompanied by an immunomodulating activity (37). Notably, in our study, fosfomycin was active against all the ESBL-producing E. coli and K. pneumoniae isolates.…”
supporting
confidence: 54%
“…There is some evidence that fosfomycin might be a promising solution for the treatment of such infections (19,20,30). It is also suggested that the antimicrobial activity of fosfomycin against ESBL-producing E. coli may be accompanied by an immunomodulating activity (37). Notably, in our study, fosfomycin was active against all the ESBL-producing E. coli and K. pneumoniae isolates.…”
supporting
confidence: 54%
“…The latter effect of fosfomycin has been demonstrated on neutrophils derived from immunocompromised patients [92,93].…”
Section: Of 27mentioning
confidence: 95%
“…Fosfomycin also exhibits an immunomodulatory effect on B-cell activation (22). Fosfomycin enhances neutrophil phagocytic killing of invading pathogens (23), even in patients on chronic hemodialysis and renal transplantation (24). Fosfomycin resulted in enhanced bactericidal ability of neutrophils compared to other antimicrobials (25).…”
Section: Immunomodulating Activitymentioning
confidence: 99%